The Supervising Role of the Apron Movement Control (AMC) Unit on Aviation Security and Safety at Pattimura Ambon International Airport - Hitimala, Aghaiif; Yudianto, Kifni (Journal of Citizen Research and Development, 2024)
Security and safety are crucial factors in aviation activities, considering the sensitivity of air transportation that requires assurance of safety at all times. The success of the AMC unit's tasks and responsibilities is measured by their ability to optimize supervision, thus creating safe and secure conditions, in accordance with applicable regulations. This study aims to evaluate the role of the AMC unit in ensuring security and safety in the airside area of Pattimura Ambon International Airport and to identify obstacles in supervision in the area. The approach used in this study is descriptive qualitative. The data collected consists of primary and secondary data. Primary data is obtained through observation and interviews, while secondary data comes from literature studies and photographs related to the problem being studied. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, triangulation techniques are used. The research was conducted in March 2024. The results of the study indicate that the AMC unit at Pattimura Ambon International Airport has carried out supervision well in accordance with the standard operating procedures PM-IK (Quality Procedures and Work Instructions). Supervision covers four components of the work area: Airport Operation Control Center (AOCC), Data Entry, Field Inspection, and Aviobridge Operations. Supervision is carried out through inspections every two hours for FOD and fuel spills, supervision of aircraft movements and engine running up/idle, GSE vehicle speed, and worker compliance with the use of Personal Protective Equipment. The AMC unit strives to implement the 3S+1C principle (Safety, Security, Service, and Compliance). The obstacles faced include a shortage of personnel, which causes an increase in workload and less than optimal supervision, as well as violations by service users or workers in the airside area, which have the potential to cause accidents.